2017
DOI: 10.1155/2017/1948241
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Biomaterials in Periodontology and Implant Dentistry

Abstract: Material is a crucial factor for the restoration of the tooth or periodontal structure in dentistry. Various biomaterials have been developed and clinically applied for improved periodontal tissue regeneration and osseointegration, especially in periodontology and dental implantology. Furthermore, the biomimetic approach has been the subject of active research in recent years. In this review, the most widely studied biomaterials (bone graft material, barrier membrane, and growth or differentiation factors) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 92 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…The average surface roughness produced by the laser-treated acid-etched implant is around 2.28 μm. Studies have shown an increase in bone formation around such implant surfaces which lead to the formation of titanium nitride on the surface [8].…”
Section: Laser Treatmentsmentioning
confidence: 99%
“…The average surface roughness produced by the laser-treated acid-etched implant is around 2.28 μm. Studies have shown an increase in bone formation around such implant surfaces which lead to the formation of titanium nitride on the surface [8].…”
Section: Laser Treatmentsmentioning
confidence: 99%
“…Although guided tissue regeneration (GTR) promotes periodontal membrane reattachment and epithelial reconstruction [ 3 ], conventional GTR promotes neither the differentiation and maturation of osteoblasts nor the regeneration of alveolar bone. A controlled-release drug delivery system can prolong the time that drugs remain in the affected area, segment the administration of medications, and facilitate a timed, quantitative, and uniformly targeted treatment [ 4 ]. For example, bone morphogenetic protein-2 (BMP-2) hydrogels with chitosan (CS) have been found to induce new alveolar bone formation, promote jaw healing, and guide periodontal tissue regeneration [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, traditional bone allografts and alloplastic biomaterials used in dentistry have limited capacity to stimulate bone regeneration, and fundamentally act as osteoconductive materials. In addition, the need of treating alveolar bony defects with different shapes, sizes, and with limited anatomic accessibility has focused the interest in gel-state biomaterials [2,3]. Hydrogels consist of water-swollen nets of cross-linked polymer chains.…”
Section: Introductionmentioning
confidence: 99%